2004
DOI: 10.1021/ja0351490
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity of Four-Membered-Ring 6π-Electron Systems:  N2S2 and Li2C4H4

Abstract: N(2)S(2) is a four-membered-ring system with 6pi electrons. While earlier proposals considered N(2)S(2) to be aromatic, recent electronic structure calculations claimed that N(2)S(2) is a singlet diradical. Our careful reexamination does not support this assertion. N(2)S(2) is closed shell and aromatic since it satisfies all three generally accepted criteria for aromaticity: energetic (stability), structural (planarity with equal bond lengths), and magnetic (negative nucleus-independent chemical shift due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
120
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(138 citation statements)
references
References 60 publications
15
120
1
2
Order By: Relevance
“…However, large LUMO occupation numbers indicated the presence of a strong antibonding effect which caused a 7% reduction to the aromatic character of S2N2. The conclusions of Jung et al 25 are for the most part in agreement with our recent high level ab initio analysis of the electronic structure of S2N2, as we also found it to be a primarily aromatic system. 16 Our detailed wave function analysis showed that S2N2 possesses 6% diradical character which could be attributed to the nitrogen atoms.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…However, large LUMO occupation numbers indicated the presence of a strong antibonding effect which caused a 7% reduction to the aromatic character of S2N2. The conclusions of Jung et al 25 are for the most part in agreement with our recent high level ab initio analysis of the electronic structure of S2N2, as we also found it to be a primarily aromatic system. 16 Our detailed wave function analysis showed that S2N2 possesses 6% diradical character which could be attributed to the nitrogen atoms.…”
supporting
confidence: 92%
“…16 Our detailed wave function analysis showed that S2N2 possesses 6% diradical character which could be attributed to the nitrogen atoms. This value is in good agreement with the antibonding effect discussed by Jung et al 25 However, they do not directly relate the antibonding effect to the diradical character in their conclusions.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…However, simple total electronic counts lead sometimes to incorrect results [14,[53][54][55]. In addition, electron counting does not provide a quantitative value, so comparisons of aromaticity from different compounds are not possible.…”
Section: Introductionmentioning
confidence: 99%